Some new Black Mildew, Asterina, collected from North -Western U.P. - Nomani, M A; Tripathi, S C (Recent Research in Science and Technology, 2013)
During the morphotaxonomic studies of Black Mildews from Himalayan foothills of North-Western Uttar Pradesh, 20 species of Asterina were collected. Out of these, Asterina syzygicola collected on Syzygium jambolanum and Asterina heniana collected on Syzygium henianum are described and illustrated as new to science